2006
DOI: 10.1097/01.bsd.0000210119.47387.44
|View full text |Cite
|
Sign up to set email alerts
|

Success and Safety in Outpatient Microlumbar Discectomy

Abstract: Currently, many spine surgeons perform microlumbar discectomies on an outpatient basis. Yet, it is often customary for patients to have a 1-night stay in the hospital. Many studies have shown the efficacy of microlumbar discectomy (MLD) and its preference among surgeons for the treatment of lumbar disc herniation. It has also been shown to be safe, successful, and cost-effective. However, a large comprehensive study of this magnitude, gauging safety, success, and patient satisfaction for these procedures on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…A large study performed by a single orthopedic spine surgeon demonstrated an admission rate of 1.7%. 13 This is consistent with the 1.2% admission rate amongst the spine surgeons in this study. The most valuable measure of admission rates for the purpose of this study would be to isolate those that were secondary to a surgical complication.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…A large study performed by a single orthopedic spine surgeon demonstrated an admission rate of 1.7%. 13 This is consistent with the 1.2% admission rate amongst the spine surgeons in this study. The most valuable measure of admission rates for the purpose of this study would be to isolate those that were secondary to a surgical complication.…”
supporting
confidence: 81%
“…A key factor influencing early discharge of patients undergoing outpatient microdiscectomy is anesthetic complications such as pain, nausea, vomiting and ocular complications. [12][13][14] Occasionally, patients are admitted due to social reasons such as lack of caregiver at home. 8 Admission rates can also be largely influenced by the individual surgeon's comfort level.…”
mentioning
confidence: 99%
“…Given that many studies have proved ASCs produce cost savings with equivalent safety compared with hospitals, any perceived conflict of interest related to the financial relationship of physicians to ASCs must be considered in light of the confluence of interest among stakeholders created by such efficiencies. 1,6,11,16,22 Our initial experience with 1-and 2-level outpatient ACDF surgery in patients with ASA Class I and Class II provided experience and evidence to support the adoption of outpatient ACDF only under specific parameters. Presently, patients who may require conversion to corpectomy due to ossification of the posterior longitudinal ligament or migrated disc fragments, those who require revision ACDF and neck dissection through scar tissue, or those with comorbidities related to altered airway or neck anatomy are not considered for outpatient ACDF regardless of ASA classification.…”
mentioning
confidence: 99%
“…6,8,10,18 Evidence is growing that supports the safety and effectiveness of ASCs for lumbar decompression and discectomy; however, evidence for the safety and value of outpatient ACDF remains scarce. [1][2][3]16,20,25 Although short-term costs to health care providers, third-party payers, and health care purchasers tend to be lower in ASCs, cost savings will only be realized across the entire outpatient care episode if that care is associated with surgical safety on par with safety in inpatient settings. Cheaper surgical care up front will lose its value if associated with decreased safety and elevated downstream costs of complications and readmissions.…”
mentioning
confidence: 99%
“…[1][2][3]11,14,19 Surgical costs to the health care provider, the third-party payer, and the health care purchaser are less in the ASC setting, but these cost savings will only be realized across the care episode if the ASC setting provides equivalent (or superior) surgical quality. Therefore, the demonstration of equivalent surgical safety and quality is necessary to determine the relative value (quality/cost) of outpatient versus inpatient ACDF.…”
mentioning
confidence: 99%